Perilaku Komunikasi Pengguna Media Sosial Tantan dalam Menjalin Relasi Pertemanan: (Studi Pada Mahasiswa Universitas Syiah Kuala Banda Aceh) - Nadia Muharman; Riska Wahyuni (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2019)
This study entitled "The Communication Behavior of Tantan Media Social Users in Establishing Friendship (A Case Study on the Students of Syiah Kuala University, Banda Aceh).” This study aims to understand the interaction, action, and the relationship of the users in developing friendship. This study used qualitative descriptive method with a structured interview for the data collection. The theory used in this research is the mediamorphosis theory. The interviewees were chosen using purposive sampling method, and the data were analyzed using model data analysis Miles and Huberman. The research results obtained that communication behavior of the users in developing friendship was through the interviewees interaction with other users; the interviewees focus on chatting with many users in order to get more friends. The interviewees‟ relationship in Tantan social media with the chatting partners were only developed until friendship stage, and did not continue to be lovers.